Generation of maghemite nanocrystals from iron–sulfur centres. Issue 26 (5th April 2019) - Banerjee, Samya; Omlor, Andreas; Wolny, Juliusz A.; Han, Yisong; Lermyte, Frederik; Godfrey, Amy E.; O'Connor, Peter B.; Schünemann, Volker; Danaie, Mohsen; Sadler, Peter J.
Abstract : Electron beam induced generation of maghemite nanocrystals from polymer-encapsulated iron–sulfur centres. Abstract : Iron oxide nano-crystals 0.1–1.1 μm in diameter were generated on sulfur-doped amorphous carbon surfaces by electron beam irradiation of the novel 13e − high-spin complex [Fe(4-methyl-1, 2-benzenedithiolate)2 ][NHEt3 ] encapsulated in a triblock copolymer. Possible relevance to iron nano-mineralization from Fe–S ferredoxin proteins and iron dysregulation in neurological disorders is discussed.